FRI0181 Sirukumab, a human anti-IL-6 monoclonal antibody, improves physical function in patients with active ra despite methotrexate therapy: Results from a 2-part, proof-of-concept, dose-ranging, randomized, double-blind, placebo-controlled, phase 2 study. (23rd January 2014) - Hsu, B.; Chiou, C.-F.; Sheng, S.; Smolen, J.; Weinblatt, M.
Abstract : Background: Sirukumab (formerly named CNTO136) is a human mAb that binds with high affinity to the cytokine IL-6. In the proof of concept part (Part A) of this multicenter, randomized, double blind, PBO controlled, phase 2 study, 100mg sirukumab SC injections q2w were generally well tolerated and efficacious Objectives: The phase 2 dose-ranging Part B was initiated after Part A to determine efficacious and safe sirukumab dose regimens. Methods: In Part B, pts with active RA despite MTX were randomized equally to: (1) PBO q2wk at wks 0–10, then sirukumab 100 mg q2wk at wks12–24; (2) sirukumab 100 mg q2wk at wks 0–24; (3) sirukumab 100 mg q4wk at wks 0–24; (4) sirukumab 50 mg q4wk at wks 0–24; or (5) sirukumab 25 mg q4wk at wks 0–24. As reported previously, the primary endpoint (ACR50 response at wk 12) was achieved by the 100 mg q2wk and 50 mg q4wk doses. We now report specific changes observed through wk12 in the Health Assessment Questionnaire disability index (HAQ-DI), the physical component summary (PCS) score of the Short Form-36 (SF-36) scales, and individual ACR core components other than HAQ-DI. Two improvement thresholds (≥0.25 and ≥0.30) were used to define HAQ-DI response. Clinical response was assessed using the Disease Activity Score (employing 28 joints and C-reactive protein, DAS28-CRP) and Clinical Disease Activity Index (CDAI). The study was only powered for the primary endpoint. An intent-to-treat analysis of pts according to original treatment assignments was conducted, with imputation of missing data by carrying forward the last observation and treatment failure rules for non-responders. Results: In Part B, 151 pts were randomized and treated. At baseline, mean age: 53±11 yrs, mean weight: 69±15 kg, mean DAS28 (CRP): 5.9±0.9, and median serum CRP: 1.7 mg/dL. Mean baseline HAQ-DI scores (1.54±0.64) were comparable between treatment groups; mean SF-36 PCS score (31.55±7.78) was notably below the general population norm. At wk12, a higher proportion of pts achieved HAQ-DI response, significantly greater improvement in HAQ-DI was observed in the combined sirukumab group (mean±sd: 0.42±0.53) compared to PBO (0.15±0.56) (p=0.012). No apparent sirukumab dose response was observed. HAQ-DI response was observed as early as wk2 and increased over time through wk24 in all 5 treatment groups. At wk12, greater improvement in SF-36 PCS score was observed in the combined sirukumab group compared with PBO (p=0.038). Also, statistically significant improvement in the combined sirukumab group vs. PBO was observed for each of the ACR core components, except for tender joint count, which trended toward improvement (p=0.06). Pain (p=0.010), physician global (p=0.005), and CRP (p<0.001) appeared to show the greatest short-term response to sirukumab treatment. Significant clinical improvement in the combined sirukumab group vs. PBO was evident at wk12 when assessed either by change from baseline in DAS28 (CRP) (p<0.001) or by change in the CDAI score (p=0.009). Conclusions: In this Phase 2 study of patients with active RA despite MTX therapy, sirukumab in combination with MTX, improved physical function as well as reduced multiple other signs and symptoms of RA. Disclosure of Interest: B. Hsu: None Declared, C.-F. Chiou: None Declared, S. Sheng Employee of: Janssen Research & Development, LLC, J. Smolen Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, M. Weinblatt Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study